Testing new PCR primers and a TaqMan™ probe for detection of Phlyctema vagabunda syn. Neofabraea alba - Vergara, Michelle J.; Pushparajah, I.P. Shamini; Mackay, John F.; Everett, Kerry R. (New Zealand Plant Protection, 2019)
Phlyctema vagabunda syn. Neofabraea alba is a fungal pathogen that causes bull’s eye rot (BER) of apples. Polymerase chain reaction (PCR) primers complementary to the inter-transcribed spacer region of ribosomal DNA (ITS) and the ?-tubulin gene region, and a TaqMan™ probe assay were developed to detect this pathogen. These assays were compared in quantitative PCR (qPCR) reactions for amplification of DNA extracted from several fungal species and from apple tissue. Although the ITS and the ?-tubulin primers amplified all N. alba isolates, both primers also amplified a few other fungal species. The TaqMan™ probe used with published primers for N. alba only amplified N. alba isolates. The TaqMan™ assay resulted in the lowest crossing threshold (Ct) values for DNA extracted from apple fruit, leaves, and spores collected on cellophane from eight apple orchards. The TaqMan™ results were correlated with percentage BER (%BER) in a 400-apple sample harvested from the same orchards. The TaqMan™ probe assay was the most sensitive and specific qPCR protocol tested, and Ct values showed the best correlation with %BER.